2018
DOI: 10.1021/acs.est.7b05624
|View full text |Cite
|
Sign up to set email alerts
|

Determining Biodegradation Kinetics of Hydrocarbons at Low Concentrations: Covering 5 and 9 Orders of Magnitude of Kow and Kaw

Abstract: A partitioning-based experimental platform was developed and applied to determine primary biodegradation kinetics of 53 hydrocarbons at ng/L to μg/L concentrations covering C8-C20, 11 structural classes, and several orders of magnitude in hydrophobicity and volatility: (1) Passive dosing from a loaded silicone donor was used to set the concentration of each hydrocarbon in mixture stock solutions; (2) these solutions were combined with environmental water samples in gastight auto sampler vials for 1-100 days in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 33 publications
1
61
1
Order By: Relevance
“…Modifications to standard screening biodegradation tests are being explored to 1) apply such tests to UVCBs, and 2) improve the understanding of biodegradation for the constituents present in or representing those mixtures. These include the use of additional measurements, such as chemical analysis and measurement of biomass to aid interpretation, and passive dosing to establish suitable exposures of hydrophobic organic mixtures (Birch et al 2018; Brillet et al 2018; Brown et al 2018). It is recognized that further research is needed and that the influence of competitive effects, sequential degradation, cometabolism, and the conditions of screening tests on the results and their interpretation should be considered.…”
Section: Identification Of the Fate And Hazard Propertiesmentioning
confidence: 99%
“…Modifications to standard screening biodegradation tests are being explored to 1) apply such tests to UVCBs, and 2) improve the understanding of biodegradation for the constituents present in or representing those mixtures. These include the use of additional measurements, such as chemical analysis and measurement of biomass to aid interpretation, and passive dosing to establish suitable exposures of hydrophobic organic mixtures (Birch et al 2018; Brillet et al 2018; Brown et al 2018). It is recognized that further research is needed and that the influence of competitive effects, sequential degradation, cometabolism, and the conditions of screening tests on the results and their interpretation should be considered.…”
Section: Identification Of the Fate And Hazard Propertiesmentioning
confidence: 99%
“…Such passive dosing systems could provide an alternative to oiled gravel dosing systems (Carls et al ; Heintz et al ; Brannon et al ; Jung et al ; Adams et al ), enabling collection of toxicity data to support calibration and validation of models that reliably predict effects under dynamic exposure conditions characteristic of actual spill scenarios. Recent work has also demonstrated the utility of passive dosing methods to investigate degradation processes of defined mixtures of individual hydrocarbons (Birch et al ). Thus, another logical extension is to explore the use of passive dosing in improving our understanding of oil fate processes.…”
Section: Summary and Future Applicationsmentioning
confidence: 99%
“…Further detailed assessment of a subset of inocula (sites 4 and 7) found that most of the total biodegradation (91-95%) occurred within the first week of incubation, suggesting phenanthrene rapidly biodegrades in water. In other non-standard studies, phenanthrene biodegradation has been measured in both fresh and marine water at low, environmentally relevant, concentrations [64,65]. Phenanthrene was passively dosed through a loaded polymer as part of a composed mixture.…”
Section: Experimental Data For the Water Compartmentmentioning
confidence: 99%
“…Phenanthrene was evaluated using the QSAR model BioHCwin (v1.01), which has been developed specifically for the biodegradation half-life prediction of petroleum hydrocarbons [51]. Recent comparisons of BioHCwin predictions to experimental half-lives have found predictions to be conservative [64,129]. Phenanthrene was assessed to be within the applicability domain of the model (Additional file 1: Section S3), and has a predicted half-life of 15.0 days.…”
Section: Other Information Useful In a Weight-of-evidence Approach Inmentioning
confidence: 99%